Ubiquitous Computing and Multimedia Applications Second International Conference, UCMA 2011, Daejeon, Korea, April 13-15, 2011. Proceedings, Part I - Kim, Tai-hoon; Adeli, Hojjat; Robles, Rosslin John; Balitanas, Maricel (Communications in Computer and Information Science,, 2011)
This two-volume set (CCIS 150 and CCIS 151) constitutes the refereed proceedings of the Second International Conference on Ubiquitous Computing and Multimedia Applications, UCMA 2011, held in Daejeon, Korea, in April 2011. The 86 revised full papers presented were carefully reviewed and selected from 570 submissions. Focusing on various aspects of advances in multimedia applications and ubiquitous computing with computational sciences, mathematics and information technology the papers present current research in the area of multimedia and ubiquitous environment including models and systems, new directions, novel applications associated with the utilization, and acceptance of ubiquitous computing devices and systems.